PENGARUH STATUS SOSIAL EKONOMI, GENDER, BUDAYA TERHADAP NIAT BERWIRAUSAHA SISWA SMK DI KECAMATAN LEGOK (STUDI PADA SMK PGRI 31 LEGOK DAN SMKN 12 KAB. TANGERANG) - Afifah Azzahrah; Khusaini Khusaini; Sri Lestari (Journal of Business Education and Social, 2021)
This research was conducted with the aim of knowing the effect of factors of socioeconomic status, gender, culture on the entrepreneurial intentions of SMK students in Legok District. The population in this study were grade 12 students at SMK PGRI 31 Legok and SMKN 12 Kab. Tangerang, totaling 530 students. Sampling was carried out using the Simple Random Sampling technique with a total sample of 84 students. Data collection techniques using online questionnaires (google form) multiple regression analysis. The results of the study show that partially, socioeconomic status and gender have no effect on entrepreneurial intentions, while culture has a significant influence on entrepreneurial intentions. Meanwhile, it simultaneously shows that socio-economic status, gender, and culture have a significant effect on students' entrepreneurial intentions. Keywords: Socio-Economic Status, Gender, Culture, Entrepreneurial Intention